Physiological benchmarks and player profiling in elite football: A role-specific analysis using T-scores - Manzi, V.; Cardinale, D. A.; Perrone, M. A.; Bovenzi, A.; Iellamo, F.; Savoia, C.; Caminiti, G.; Laterza, F. (Sports, 2025)
Physiological characteristics such as VO2max, running economy (RE), maximal aerobic speed (MAS), maximal sprinting speed (MSS), anaerobic speed reserve (ASR), and player profiling (based on MSS and MAS) have been proven to be important for training prescriptions in football. However, previous studies on player profiling have neglected the absolute values of MSS and MAS. The objectives of this study were to compare the aforementioned physiological variables among player roles, create benchmarks, and provide normative data to help coaches categorize players, ultimately proposing a new player profiling method. We analyzed 195 male professional football players (50 forwards, 59 midfielders, 44 full-backs, and 42 center-backs). Multivariate analysis of variance with Tukey`s post hoc tests revealed positional differences. Center-backs exhibited lower VO2max than midfielders and full-backs. Both center-backs and forwards showed poorer RE and MAS compared to midfielders and full-backs. Full-backs achieved higher MSS than midfielders and center-backs, and forwards outperformed center-backs. Finally, midfielders demonstrated lower ASR than all other positions. Benchmarks based on T-scores for all variables were provided. Finally, in the new profiling method proposed—also based on T-scores—players were classified as "speed", "endurance", or "hybrid" if their MAS and/or MSS T-score exceeded 60, "in development" if both were below 45, and "average" if both scores were between 45 and 60 without any value above 60. The normative data provided can assist coaches in identifying specific areas for improvement in players` physical conditioning—particularly valuable for youth athletes or those returning from injury. Additionally, the new profiling method offers insights into individual player characteristics, enabling more tailored and effective training interventions.